Urban Regeneration through Creativity and Circular Economy. The case of Mediterranean Historic Cities. - Avgerinou Kolonia, Sofia; Gounaridis, Konstantinos (Technical Annals, 2025)
Contemporary cities face mounting pressures from climate change, resource depletion, and the fragility of existing urban systems. Circular economy principles are increasingly framed as a response, yet their application in urban contexts is far from straightforward. Rather than a fixed model, circularity emerges as a framework that may reshape production and consumption through practices of Reuse, Repair, Recycling, and upcycling. At the same time, it exposes political tensions, uneven capacities, and unresolved questions about who benefits from such transitions. European examples - Amsterdam’s city-wide strategy, Prato’s textile-based networks, or Satakunta’s industrial heritage - illustrate how local histories and governance arrangements shape implementation. Amsterdam’s rhetoric of transformation, for instance, coexists uneasily with growth-driven logics, while Prato demonstrates how long-standing textile recycling traditions can inform contemporary circular planning. Outside Europe, cities such as Santiago and Nablus(Palestine) reveal how circular practices often rely on informal networks and community knowledge rather than institutional frameworks. These variations highlight both the promise and the limits of transferring models across regions. A recurring pattern is the so-called implementation gap: pilot projects abound, yet comprehensive systemic change remains elusive. Factors include fragmented regulations, short political cycles, and difficulties aligning ecological ambitions with social and economic needs. Small-scale creative and cultural enterprises, in Mediterranean cities, and especially in Athens, appear to offer fertile ground for experimentation, linking craft traditions with digital tools and localized reuse practices. Still, their contributions are precarious and easily overshadowed by capital-intensive solutions. The text ultimately suggests that circular urbanism is less a doctrine than an ongoing negotiation between preservation and innovation, equity and competitiveness, continuity and change. ΕU Mediterranean projects such as INNOMED-UP and CARISMED, led by the National Technical University of Athens, show that modest interventions- smart bins, adaptive reuse, cross-border exchanges - can generate incremental shifts, but sustainable progress will likely depend on context-sensitive governance and the active participation of local communities.